Comparison of Gaps in noise test (GIN) in adults with normal and conductive hearing loss - Vahid Mehdizadeh; Masumeh Rouzbahani; Jalal Sameni; Mohammad Hossein Nilforoush; Parvaneh Mahdi; Hamid Haghani (Vesnu Publications, 2013)
Abstract   Introduction: conductive hearing loss attenuates and delays sound transmission in the middle ear. It can make variety of central auditory processing disorders; that persists even after resolve of peripheral auditory system problems. One of the aspects of central auditory processing is the temporal processing, which is important for understanding speech, including temporal resolution, temporal ordering, temporal integration and temporal masking. In this study to assess effects of conductive hearing loss on the ability temporal resolution, the gap in noise test is used. Materials and methods: This noninvasive analytic-prescriptive study was conducted on 13 persons with bilateral slight to moderate conductive hearing loss and 13 persons with normal hearing between 20-50 years old in similar age and sex condition. Approximate threshold and percent of correct answers in GIN test obtained, then analyzed with nonparametric mann-whitney, Wilcoxon tests and between two groups were compared. Results: There was no meaningful difference in approximate threshold and percent of correct answers between two gender and test ear in each group (p>0.05). While mean approximate threshold of people with conductive hearing loss was significantly (P=0.003) more than that of the normal group and mean percent of correct answers was less than normal group (right ear P=0.000 ,left ear P=0.000). Conclusion: The conductive hearing loss with increase in approximate threshold and decrease in percent of correct answers has effect on the part of central auditory pathway and reduces ability of temporal resolution. keywords: conductive hearing loss, Gaps in noise (GIN) test, temporal resolution